MANAJEMEN KONFLIK DALAM TIM EDUPRENEUR SEBAGAI KATALISATOR INOVASI DI MI - Fauzi, Hasan; Salim, Muhlisin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The purpose of this study is to analyze the forms of conflict, management strategies, and their role as catalysts for innovation within the edupreneur team at MI Roudlotul Huda Terban. The research method used was qualitative with a case study approach. Data were collected through in-depth interviews with foundation administrators, madrasah principals, and teachers, as well as participant observation and documentation studies. Data analysis followed the interactive model of Miles and Huberman. The results showed that: (1) The forms of conflict that emerged consisted of substantive conflicts, such as tensions between teachers' pedagogical visions and the foundation's commercial orientation, as well as affective conflicts resulting from generational dynamics within the team; (2) The effective conflict management strategy implemented was a collaborative approach colored by Islamic values, such as deliberation to find the best solution (mashlahah), strengthening ties, and making congregational prayer a medium for shared reflection; (3) This constructively managed conflict proved to be a catalyst that triggered a number of important innovations, including the birth of the